Dissipativity Reinforcement in Network System: A Design Principle of Large-scale Dynamical System*. Issue 22 (2016) - Urata, Kengo; Inoue, Masaki
Abstract: We analyze the dissipativity in a large-scale network system, which is composed of a large number of internally connected components. Assuming that every component has special passivity property, we show that the network system inherits the same property of the component independently of the network scale. In addition, the dissipation performance of the network system, evaluated by the H∞ norm, is gradually reinforced via network expansion. This analysis can be a fundamental principle of constructing large-scale dynamical systems.